2020
DOI: 10.1111/liv.14744
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of liver cirrhosis in individuals with hepatitis B virus infection in sub‐Saharan Africa: Systematic review and meta‐analysis

Abstract: Background & Aims Chronic hepatitis B virus (HBV) infection accounts for 30%‐50% of cirrhosis related deaths in sub‐Saharan Africa (SSA). Since HBV‐related cirrhosis is an indication for immediate antiviral therapy and cancer surveillance, we aimed to estimate the prevalence of cirrhosis among treatment‐naïve patients with chronic HBV infection in SSA. Methods We performed a systematic review of published articles which evaluated liver fibrosis stage among treatment‐naïve HBV‐infected individuals who presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
(28 reference statements)
3
7
0
Order By: Relevance
“…A systemic review and meta-analysis by Surial et al [ 29 ] reported a pooled cirrhosis prevalence of 6.1% (n = 3204) in sub-Saharan Africa, using a combination of non-invasive assessments including transient elastography, APRI score and FibroTest. The prevalence of cirrhosis in our study using the APRI and FIB-4 scores are in agreement with Surial et al [ 29 ] and with other reports from the West Africa region which have estimated the prevalence of cirrhosis among HBV mono-infected individuals as ranging from 0% (n = 26) in prisoners in the Ivory Coast [ 30 ] to 7.3% (n = 300) in blood donors in the Gambia [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…A systemic review and meta-analysis by Surial et al [ 29 ] reported a pooled cirrhosis prevalence of 6.1% (n = 3204) in sub-Saharan Africa, using a combination of non-invasive assessments including transient elastography, APRI score and FibroTest. The prevalence of cirrhosis in our study using the APRI and FIB-4 scores are in agreement with Surial et al [ 29 ] and with other reports from the West Africa region which have estimated the prevalence of cirrhosis among HBV mono-infected individuals as ranging from 0% (n = 26) in prisoners in the Ivory Coast [ 30 ] to 7.3% (n = 300) in blood donors in the Gambia [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…Although our study population consisted mainly of young HIV/HBV-coinfected individuals on tenofovir-containing ART, a significant proportion had relevant risk factors for the development of HCC: 7% had a liver stiffness measurement consistent with liver cirrhosis and 60% had a high HBV VL at the time of ART start. The prevalence of liver cirrhosis among people with HBV in our study is in line with the results of a recent meta-analysis, which showed similar estimates across SSA, and did not find evidence of a significant difference between HIV-infected and uninfected individuals (Surial et al, 2020). Interestingly, most individuals with liver stiffness compatible with cirrhosis did not have signs of liver cirrhosis on ultrasound.…”
Section: Discussionsupporting
confidence: 91%
“…Although transient elastography is considered the best method for the non-invasive measurement of liver fibrosis in individuals with HBV infection, it is rarely available in African healthcare-settings. A recent meta-analysis, including both pwHBV and pwHIV/HBV, found only seven studies across Africa reporting fibrosis using TE [ 3 ]. The pooled prevalence of significant fibrosis was 11.6%, and the estimate for cirrhosis was 6.1%, both very similar to our results.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis B virus (HBV) infection affects >10% of the general population in West Africa, and is the first cause of liver cirrhosis and cancer [ 1 , 2 ]. According to a recent meta-analysis, between 4% and 13% of people living with HBV in Africa had signs of liver cirrhosis, an indication for the immediate initiation of antiviral therapy [ 3 ]. The risk of liver-related complications in the region is further exacerbated by co-existing environmental factors, such as the exposure to aflatoxin, and co-infections with HIV, hepatitis delta or Schistosoma mansoni [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%